Effects of therapeutic horsemanship on caregiver stress scores of children with autism - Barron, Danielle C.; Craft, Madison P.; Florek, Emily R.; Stanley, Brianna N.; Stoner, Alexis M.; Paschall, Nancy A.; Newman, Sarah; Tumlin, Kimberly I. (Frontiers in Psychiatry, 2025)
IntroductionCaregivers (primarily parents) of children with autism spectrum disorder (autism) report higher levels of stress, burn out and depression when compared to caregivers of children without autism. Interventions which incorporate animals have been efficacious in improving well-being for children with autism; however, investigating how caregivers are affected when their children are involved in such programs are a nascent field of inquiry. The objective of this pilot study is to characterize emotional strain and stress in caregivers of children with autism when their child attended a therapeutic horsemanship (TH) program.MethodsThirteen caregiver-child dyads completed the study. Utilizing a mixed methods approach, caregivers completed the Depression Anxiety Stress Scale (DASS-21) questionnaire prior to and upon completion of their child’s participation in TH for a 16-week semester. Semi-structured interviews were performed once during the semester and transcripts were analyzed using thematic analysis.ResultsWe observed caregivers experienced a statistically significant decrease (p=0.03) in their stress levels over a single semester of TH participation demonstrated by a reduction in DASS-21 stress subcategory (pre intervention mean 12.77 (SD = 9.95), post-intervention mean 8.62 (SD = 10.98). A total of five common themes were identified from the caregivers’ interview responses. Of these, four were associated with increased caregiver stress and strain: 1) navigating the care and management of their child’s diagnosis; 2) the lack of resources for their child with autism (CWA); 3) managing finances; and 4) caring for more than one child in their household. In contrast, the fifth theme captured a reduction in caregiver stress and strain secondary to their indirect involvement in TH.DiscussionThis pilot study successfully captured the indirect effects of a TH program in caregivers of children with autism. Integral to understanding caregiver stress, this study further characterizes how caregiver emotional stress and strain can be impacted as their child builds life skills in TH.